2007
DOI: 10.1158/1055-9965.epi-07-0042
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Germ Cell Tumors among Men with HIV/Acquired Immunodeficiency Syndrome

Abstract: Background: Men with HIV/acquired immunodeficiency syndrome (AIDS) are reported to be at increased risk for germ cell tumors (GCT), particularly testicular seminoma. We investigated correlates of this association to improve understanding of GCTs. Methods: Testicular and extratesticular seminoma and nonseminoma cases were found by linking population-based cancer and HIV/AIDS registry data for 268,950 men who developed AIDS in 1980 to 2003. Standardized incidence ratios (SIR) with 95% confidence intervals (95% C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 24 publications
1
29
0
4
Order By: Relevance
“…8 Additionally, several genitourinary malignancies have been demonstrated to have an increased incidence in the HIVpositive population, including testicular seminoma and renal cell carcinoma. [8][9] This has been postulated to be a result of immunosuppression; however, these interactions have yet to be fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…8 Additionally, several genitourinary malignancies have been demonstrated to have an increased incidence in the HIVpositive population, including testicular seminoma and renal cell carcinoma. [8][9] This has been postulated to be a result of immunosuppression; however, these interactions have yet to be fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…1 In addition, several genitourinary malignancies have been demonstrated to have an increased incidence in the HIV-positive population including seminoma and possibly renal cell carcinoma. 1,2 Interestingly, some malignancies such as breast cancer have been shown to occur at a reduced rate in this population. 3 According to the Centers of Disease Control, at the end of 2003 an estimated 1 039 000-1 185 000 persons in the United States were living with HIV/AIDS and about three quarters of these patients were men.…”
Section: Introductionmentioning
confidence: 99%
“…74 Despite the high prevalence of HIV infection in sub-Saharan Africa, there have been no reports of a significant increase in germ cell testicular tumors in this region. A more recent study indicated that the relative risk for testicular seminoma in HIV-positive patients compared with HIV-negative individuals is around 2.…”
Section: Testicular Tumorsmentioning
confidence: 99%